Effects of trace element addition on process stability during anaerobic co-digestion of OFMSW and slaughterhouse waste. (January 2016) - Moestedt, J.; Nordell, E.; Shakeri Yekta, S.; Lundgren, J.; Martí, M.; Sundberg, C.; Ejlertsson, J.; Svensson, B.H.; Björn, A.
Highlights: Combined effect of essential trace elements are illustrated. Cobalt addition can decrease process stability during Nickel shortage. Cobalt and Nickel addition result in higher process stability. Viscosity and gas kinetics can be used to measure process stability. Abstract: This study used semi-continuous laboratory scale biogas reactors to simulate the effects of trace-element addition in different combinations, while degrading the organic fraction of municipal solid waste and slaughterhouse waste. The results show that the combined addition of Fe, Co and Ni was superior to the addition of only Fe, Fe and Co or Fe and Ni. However, the addition of only Fe resulted in a more stable process than the combined addition of Fe and Co, perhaps indicating a too efficient acidogenesis and/or homoacetogenesis in relation to a Ni-deprived methanogenic population. The results were observed in terms of higher biogas production (+9%), biogas production rates (+35%) and reduced VFA concentration for combined addition compared to only Fe and Ni. The higher stability was supported by observations of differences in viscosity, intraday VFA- and biogas kinetics as well as by the 16S rRNA gene and 16S rRNA of the methanogens.